(untitled) (ARTEKS : Jurnal Teknik Arsitektur, 2025)
The study of circumambulation has predominantly focused on rightward or clockwise movements (pradaksina), while leftward movements are rarely discussed. In Indonesian society, physical space movement activities have been an obscured concept, necessitating exploration and presentation as a valuable aspect of Indonesian architectural knowledge. This article explores the circumambulation concepts of prasawiya (counterclockwise) and purwadaksina (clockwise) in Balinese society. Employing a qualitative approach with an ethnographic strategy, the study reveals: (1) the local Balinese term for circumambulation is pemuteran; (2) prasawiya precedes purwadaksina; (3) prasawiya signifies ascending, while purwadaksina signifies descending on the vertical axis; (4) prasawiya denotes cleansing, whereas purwadaksina denotes sacralizing; (5) the interplay between prasawiya and purwadaksina fosters dualism-harmony; (6) the pemuteran of prasawiya-purwadaksina generates the concept of empty space, specifically karang and rong. Karang precedes the presence of pelinggih, while rong emerges after its establishment, both embodying the rwa-bhineda space concept; and (7) pemuteran, rooted in the Mandhara Giri myth, underpins the orientation of kaja-kelod and kangin-kauh. Fundamentally, the world’s axis orientation is represented through the empty spaces of karang and rong.